2023
DOI: 10.3389/fped.2023.1098067
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors that influence the occurrence of otitis media with effusion in pediatric patients with adenoid hypertrophy

Abstract: ObjectiveAdenoid hypertrophy (AH) and otitis media with effusion (OME) are common pediatric otolaryngological diseases and often occur concurrently. The purpose of this study was to comprehensively analyze the factors that influence the occurrence of OME pediatric patients with AH.MethodsPatients younger than 12 years with AH, who were hospitalized for treatment at Beijing Tsinghua Changgung Hospital in Beijing, China, between March 2018 and February 2022 were enrolled. The patients were divided into an AH gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…In addition, we confirmed the reports that other authors have already shown regarding the relationship between adenoid hypertrophy and the presence of effusion in the middle ear confirmed by tympanometry examination or adenoid size and sleeping with the mouth open [43][44][45][46][47]. The high convergence of the obtained results and the resulting correlations with previous studies by other authors indicate that the studied group is representative.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we confirmed the reports that other authors have already shown regarding the relationship between adenoid hypertrophy and the presence of effusion in the middle ear confirmed by tympanometry examination or adenoid size and sleeping with the mouth open [43][44][45][46][47]. The high convergence of the obtained results and the resulting correlations with previous studies by other authors indicate that the studied group is representative.…”
Section: Discussionsupporting
confidence: 91%